Synthesis and characterization of two new cyclobutyl and aryl hydroxyethyl methacrylate monomers and their polymers - Coskun, M; Demirelli, K; Erol, I; Ahmetzade, M (John Wiley & Sons Inc, 1997)
Two new hydroxyethyl methacrylates having aryl and cyclobutane rings were synthesized by addition to 1-(epoxyethyl)-3-aryl-3-methylcyclobutane to methacrylic acid. The monomers prepared are 2-(3-methyl-3-phenylcyclobutyl)-2-hydroxyethyl methacrylate (PCHEMA) and 2-(3-methyl-3-mesitylcyclobutyl)-2-hydroxyethyl methacrylate (MCHEMA). Both monomers were polymerized at 60 degrees C in 1,4-dioxane solution using benzoyl peroxide as initiator. Poly(PCHEMA) and poly(MCHEMA) and their monomers were characterized by FT-IR and H-1- and C-13-NMR techniques. Weight average molecular weights of the polymers were determined for poly(PCHELMA) poly(MCHEMA) by gel permation chromatography. Thermal stabilities of the polymers were essentially the same. Glass transition temperatures for poly(PCHEMA) and poly(MCHEMA) were determined as 105 and 137 degrees C, respectively. No changes of the polymers by irradiation with UV light at 254 nm were observed. (C) 1997 John Wiley & Sons, Inc.
Keywords: Poly(2-Hydroxyethyl Methacrylate); 2,3-Epoxypropyl Methacrylate; Photocrosslinkable Compounds; Functional Monomers; Model Compounds; Polymerization; Acid; Copolymers; Telomers; Ring